The Influence of Education Level and Attitudes on the Quality of Public Services at the Faculty of Education, Manado State University - Meyer Rumondor, Joury; Masengi, Evi; Mokat, Jetty (International Journal of Social Science, Education, Communication and Economics, 2024)
The aim of this research is first to determine the effect of education level on the quality of public services at the Faculty of Education, Manado State University. Second, to determine the influence of Attitude on the Quality of Public Services at the Faculty of Education, Manado State University, and third, to determine the influence of Education Level and Attitude together on the Quality of Public Services at the Faculty of Education, Manado State University. This research uses quantitative methods and the number of samples to be studied is 38 people. The results of this research are that there is a partially significant influence of education level on the quality of public services. This means that if a person's education level is higher, the quality of public services at the Faculty of Education, Manado State University will also increase. There is a partially significant influence of work attitude on the quality of public services at the Faculty of Education, Manado State University. This means that if attitude gets better, the quality of public services at the Faculty of Education, Manado State University will also increase. There is a significant simultaneous influence of the level of education and attitudes on the quality of public services at the Faculty of Education, Manado State University, which means that if the level of education and attitudes are increased, then the quality of public services at the Faculty of Education, Manado State University will also increase.